Ivan Nabergoj - nesojeni župan tržaških Slovencev (1873-1897) - Čok, Štefan (Studia Historica Slovenica, 2017)
The article deals with the figure of Ivan Nabergoj, the most prominent Slovenian politician from Trieste in the second half of 19th century. The purpose is to show the role played by Nabergoj, with a major attention to the point of view of the Italian Liberal Nationals, the major political adversaries of Nabergoj that ruled the city in the period. To obtain this result the research on the Italian liberal newspapers published in Trieste has played a fundamental role, showing that for the Italian politicians Nabergoj was not only an adversary but also a symbol that had to disappear to reinforce of an Italian-only city.
Keywords: 19.st.; Avstro-Ogrska; Nabergoj, Ivan; nacionalno vprašanje; Primorska; Slovenci; slovenski politiki; Trst